Clinical Outcomes and Mortality in Elderly Heamodialysis Patients - لايقة, عنان (Latakia University Journal -Medical Sciences Series, 2020)
To evaluate the clinical outcomes and identify the predictors of mortality in elderly patients undergoing Heamodialysis. We conducted a prospective study including incident heamodialysis cases in patients 65 years of age treated during one year (2019). Demographic and clinical data on the initiation of dialysis and the clinical events during the study period were collected. Overall and technique survival rates were analyzed. RESULTS: Forty patients who began hemodialysis during the study period were considered for analysis. During the follow-up period, 22 patients died (55%). Causes of death included cardiovascular events (45%) and sepsis. The mean patient survival time was 125 days, Mortality was higher in elderly patients. Factors affecting mortality in elderly patients included advanced age, the presence of comorbid diseases and low albumin levels.